XIV—Psychopathic Agency and Prudential Deficits. Issue 3 (October 2013) - Watson, Gary
Abstract : Philosophical discussions of psychopathy have been framed primarily in terms of psychopaths' conspicuous moral shortcomings. But despite their vaunted 'egocentricity', another prominent trait in the standard psychopathic profile is a characteristic failure to look after themselves; in an important way, psychopaths appear to be as careless of themselves as they are of others. Assuming that the standard profile is largely correct, the question is how these moral and prudential deficits are related. Are they linked in some non‐accidental way? This paper is a sympathetic exploration and articulation of the hypothesis that psychopathy involves an incapacity for critical distance from from one's own impulses and inclinations, an incapacity that would explain the lack of both prudential and moral regard.